THE CHARACTERISTICS OF TEACHER’S FEEDBACK IN SPEAKING ACTIVITY OF THE GRADE TEN STUDENTS OF SMA NEGERI 20 MEDAN - Nur'aini Hakiki Nasution; Anggraini Thesisia Saragih; Muhammad Natsir (Universitas Negeri Medan, 2021)
THE CHARACTERISTICS OF TEACHER’S FEEDBACK IN SPEAKING ACTIVITY OF THE GRADE TEN STUDENTS OF SMA NEGERI 20 MEDAN *Nur’aini Hakiki Nst **Anggraini Thesisia Saragih, M.Hum. **Dr. Muhammad Natsir, M.Hum. ABSTRACTS Nasution. Nur’ aini Hakiki. Registration Number: 2132121037. The Characteristics of Teacher’s Feedback in Speaking Actvity of the Grade Ten Students of SMA N 20 Medan. English Education Program, Universitas Negeri Medan, 2020. The objective of this study were; (1) To describe types of teacher’s feedback in the speaking activities of the tenth grade students of SMA N 20 Medan, (2) To describe the students’ perception of the feedback given by the teacher in the speaking activities of the tenth grade students of SMA N 20 Medan, and (3) To analyses how does the teacher give feedback in speaking activities of the tenth grade students of SMA N 20 Medan. This study was conducted by using Research was designed through two stages; gathering information and analyzing data. The subject of the study was Grade X of SMA N 20 Medan. The instruments of data collection was gathered by distributing questionnaire and administrating interview. The study conducted distributing questionnaire to 30 respondents of the students and administrating interview to the English teacher and students. The questionnaire and interview results proved that the students need the teacher’s feedback which can motivate the students to understand about the speaking activity. Observations were done by attending the speaking classes and making field notes of all what happened in the classroom setting during the speaking learning and teaching process. With the help of audiorecorder, the researcher recorded all the speech events of the classroom community members under observation. This audio recording technique enabled the researcher top reserve the authenti city of the data. To gain comprehensive and accurate data, the researcher crosschecked the data obtained by comparing these data with those which were obtained by interviewing some of the students and the English teacher involvedin the research. The researcher also distributed the questionnaire to all of the students in the class. These accurate data where then (1) transcribed, (2) read, (3) identified,(4) categorized, and (5) analyzed to answer the research questions as those which were mentioned in the formulation of the problem. To check the trustworthiness of the data, triangulation was also used. The researcher compared the gathered data withot her relevant researches and theories and consulted the lecturers involved in thestudy. Based on the analysis of teacher’s feedback, it is figured out that the teacher mostly gave feedback in the form of explicit corrections. Also, the teacher’s feedback focused more on the phonological errors, especially pronunciation. Keywords: Speaking activity, teacher’s feedback, Research.